STRATEGI PRIORITAS PERBAIKAN KUALITAS BATIK LUMAJANG SEBAGAI IKON DAERAH BERDASARKAN PERSEPSI DAN HARAPAN MASYARAKAT DI KABUPATEN LUMAJANG - Hesti Budiwati (UNEJ e-Proceeding)
Batik is a legacy of indigenous peoples in Indonesia, which in ancient times could only be used by the royal family or the nobility alone. The facts show that batik is now a public fashion trends. The existence of batik is still relatively stagnant and less able to thrive. Therefore, the study aims to determine the strategy of quality improvement priority to batik Lumajang that the government and businesses batik Lumajang can take action priorities for the development of batik Lumajang be better. The approach used in this research is Lean Six Sigma, with a sample of 60 people Lumajang. They will be asked them to comment on batik Lumajang based on perceptions, expectations and their interests. On the basis of perceptions, expectations, and concerns of Lumajang that is structured batik Lumajang quality improvement priority areas of Lumajang as icons. The results of research, there are 5 (five) priority quality improvement batik Lumajang should precedence, that are (1) The design and product diversity batik, (2) The Batik ability to absorb perspiration, (3) The understanding of the quality of raw materials batik, (4) The quality color durability, and (5) The raw material quality batik where people yearn to raw material quality batik Lumajang.